An analysis of photovoltaic/supercapacitor energy system for improving self-consumption and self-sufficiency. (November 2022) - Hassan, Qusay; Jaszczur, Marek; Abdulateef, Ammar M.; Abdulateef, Jasim; Hasan, Ali; Mohamad, Abdulmajeed
Abstract: This research study evaluates the use of a supercapacitor module as a fast-response energy storage unit to improve energy self-consumption and self-sufficiency for renewable energy systems applications. The designed system consists of the photovoltaic component with 3.0 kWp capacity combined with (0–5) supercapacitor module with a capacity of 500F-2.7V per module to serve the desired load. The analysis was carried out using experimental data for the electrical load and solar irradiance, as well as ambient temperature at a 1-minute temporal resolution for the year 2020. The measured daily average power of the electrical load was 0.299 kW, with a daily energy consumption of 7.2 kWh/day at a maximum peak of 5.36 kW, while the yearly energy consumption was recorded 2620 kWh/year. The measured daily average solar irradiance was 3.1 kWh/m 2 /day, and the monthly average ambient temperature was 10.7 °C . The charge of the supercapacitor was only possible from the photovoltaic system and not from grid. The simulation results demonstrated that the use of the supercapacitor module could feed the rapid peaks of electrical load and significantly increase energy self-consumption and self-sufficiency. Using only five supercapacitor modules increases the annual self-consumption from 21.75% to 28.74% and the percentage of self-sufficiency increases from 28.09% to 40.77%. The study concluded that adding small and responsive energy storage is an excellent choice of batteries.